From Music Drama to Immersion: Notes on contemporary and Latin American “total art” (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The article focuses on the Wagner´s concept of Gesamtkunstwerk applied to Contemporary Art. Therefore, it deals with the interweaving of performative and visual languages and the dissolution of boundaries between stage and audience through the integration of space, in order to foster the viewer's immersion. In this way, different from the actor-spectator relationship, the theatre play is guided by the dynamics space-spectator. Finally, it analyzes works by Latin American artists, including Diego Bianchi, Marta Minujín and Tania Bruguera.
Keywords: Contemporary art; Space; Spectator